Correction Des Dissertations A L’universite Algerienne : Etude Des Pratiques Des Enseignants De Langue Française (El-Wahat Journal for Research and Studies, 2025)
Centred on the evaluation practices of Algerian university teachers, this contribution studies the tools they use for the correction of the dissertation, often introduced to evaluate the skills of their students of French. The collected answers revealed their use of criteria grids, which do not comply with the requirements: linguistic and methodological criteria give priority to the detriment of disciplinary criteria.Keywords: evaluation; dissertation; teaching practices; university; criteria.